METODE SYARAH FATH AL-BARI (Studi Syarah Hadis pada bab Halawah al-Iman) - Aan Supian (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2017)
This article  aims to find out the methods, approaches and  techniques of interpretation of Ibn Hajar’s  syarah in Fath  al-Bari  in understanding the  hadith about “halawah al-iman.” From  the  results of the  study  shows  that : First, Hadiths in chapter “halawah al-iman” contained in Fath al-Bari,  is described by the tahlili  method; Second, there are at least two approaches used, namely language approach (linguistic) and theological-normative approach; Thirdly, the Interpretation Technique used  by Ibn Hajar  in prescribing the hadith about halawah al-iman “is a technique of textual and intertextual interpretation